Metabolism of glucose activates TORC1 through multiple mechanisms in Saccharomyces cerevisiae - Alfatah, Mohammad (2024)
Target of Rapamycin Complex 1 (TORC1) is a conserved eukaryotic protein complex that links the presence of nutrients with cell growth. In Saccharomyces cerevisiae, TORC1 activity is positively regulated by the presence of amino acids and glucose in the medium. However, the mechanisms underlying nutrient-induced TORC1 activation remain poorly understood. By utilizing an in vivo TORC1 activation assay, we demonstrate that differential metabolism of glucose activates TORC1 through three distinct pathways in yeast. The first "canonical Rag guanosine triphosphatase (GTPase)-dependent pathway" requires conversion of glucose to fructose 1,6-bisphosphate, which activates TORC1 via the Rag GTPase heterodimer Gtr1GTP-Gtr2GDP. The second "non-canonical Rag GTPase-dependent pathway" requires conversion of glucose to glucose 6-phosphate, which activates TORC1 via a process that involves Gtr1GTP-Gtr2GTP and mitochondrial function. The third "Rag GTPase-independent pathway" requires complete glycolysis and vacuolar ATPase reassembly for TORC1 activation. We have established a roadmap to deconstruct the link between glucose metabolism and TORC1 activation.